Primary Hyperparathyroidism: Experience from a Tertiary Care Centre in Pakistan - Fatima, Tehseen (Pak J Med Sci, 2020)
OBJECTIVE: To study the clinical, biochemical and radiological features and management outcomes of patients with primary hyperparathyroidism. METHODS: This retrospective study was conducted at the Aga Khan University Hospital, Karachi, Pakistan and comprised data of patients with primary hyperparathyroidism from 2008 to 2017. RESULTS: Out of 103 patients, 83(80.6%) were female. Overall mean age was 59.3±16.2 years. Musculoskeletal manifestations were seen in 60(58.3%) patients and renal manifestations in 28(27.2%). Ostieits fibrosa cystica was found in 04(3.88%) patients. Overall, Ultrasound neck and sestamibi scan localized the lesion in 66 (64.1%) and 77 (76.2%) patients respectively. Among 79 patients who underwent surgery, 67 (84.8%) patients had an adenoma, 05 (6.3%) had hyperplasia and 02(2.53%) patients had parathyroid carcinoma whereas histopathology was inconclusive in 5 (6.32%) out of the 79 surgically treated patients. Disease recurrence was seen in 13 out of 79(16.45%) patients who underwent surgery. CONCLUSION: Primary hyperparathyroidism is associated with significant morbidity in our population. Targeted measures like improving patient awareness, routine calcium screening, vitamin D supplementation and a high index of suspicion by the clinician may help in early diagnosis of the condition and thus reduce morbidity.